Robotic spraying application for Fabrication Proton Exchange Membrane Fuel Cell - Ramli Sitanggang (Eksergi, 2016)
One of the processes that work in the field of engineering Proton Exchange Membrane Fuel Cell (PEMFC) is to produce a variety of designs MEA. The best design will be found in the manufacturing process. The project introduced a spray with a robotic instrument configuration x-y axis to issue MEA design. MEA layer forms which can be produced by this spray will follow a periodic function, whereas the layers including the thickness, porosity, pore diameter, specific active surface area which will be used to hold the chemical reaction to produce electricity. The character size coating layer is represented by the amount of spraying. This number is a function of the frequency of the robot, and the nozzle crosses the x-y dimensions of the substrate. Sprays produce two forms of MEA design. From the results of this study MEA quality can be assessed using a robot with a spray nozzle configuration as a contribution for Fuel Cell (PEMFC).